A novel magnetically recyclable photocatalyst of Bi12TiO20/Co composites with enhanced photocatalytic performance. Issue 17 (1st December 2017) - Wang, Yufei; Zhang, Yu; Yan, Long; Li, Jian; Wang, Chao; Fu, Feng
Abstract: Both Bi12 TiO20 and Bi12 TiO20 /Co particles were synthesized by a hydrothermal process. The as-synthesized particles were characterized by SEM and TEM for size and morphology, and the results showed the particles presented hierarchical morphology with the size of ~200 nm. Both XPS and XRD results confirmed the existence of both Bi12 TiO20 and Co phases in the Bi12 TiO20 /Co particles. The photocatalytic performance of the as-synthesized particles was investigated in Rhodamine B degradation reaction under visible light irradiation. Bi12 TiO20 /Co composites showed higher photocatalytic performance than single phase Bi12 TiO20 particles, which could be attributed to the increased separation effects between photo-induced electrons and holes from. Meanwhile, the magnetic properties of Co could be used to magnetically separate and recycle the Bi12 TiO20 /Co composites after reactions. The stability testing experiment with Bi12 TiO20 /Co particles showed that the composite had a high stability over photocatalytic corrosion. The photoelectrochemistry investigation showed that the introduction of Co could increase the electron/hole separation efficiency in BTO/Co composites during photocatalytic reactions. This research proposed an effective and inexpensive way to increase the performance and recycling of Bi12 TiO20 based photocatalysts.